Analysis of demand elasticity for processed salted fish at Maria Bintang Laut Cooperative, Diocese of Mimika, in Mimika Regency - Lakupais, Dince Dina; Iek, Mesak; Ngutra, Risky Novan (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the cost structure, revenue, income, break-even point (BEP), and demand elasticity for processed salted fish at the Maria Bintang Laut Cooperative, Diocese of Mimika, to assess business feasibility and provide strategic recommendations for income improvement. Research/methodology: The research employs a quantitative approach with a census of 60 active cooperative members out of 230 total artisans. Primary data were collected through structured interviews and field observations, while secondary data were sourced from cooperative records and government publications. Data analysis techniques include descriptive statistics, demand elasticity measurement, log-linear regression, and BEP analysis. Results: Findings indicate an increase in production from 986 kg in 2023 to 1,431 kg in 2024, alongside higher revenues (from IDR 19.72 million to IDR 35.7 million). However, despite rising revenues, the cooperative failed to reach BEP due to high production costs, especially labor and raw materials, resulting in losses in both years. The price elasticity of demand was calculated at 1.8, suggesting that demand is highly elastic, with higher prices followed by higher demand contrary to conventional economic theory but consistent with local market dynamics. Conclusions: Production and revenue rose, yet unprofitable; quality-driven demand requires pricing strategy and efficiency in labor and materials for profitability. Limitations: The study is limited by a small dataset (2023–2024), restricting statistical generalization. Contribution: This study provides practical insights for cooperatives in coastal communities to design cost efficiency, adaptive pricing, and quality-based strategies to strengthen economic sustainability.